A Pilot Controlled Feeding Trial Modifying Protein Intake in Healthy Subjects to Assess Adherence and the Metabolome. - Connolly-Schoonen, Josephine; Danowski, Lorraine; Bistricer, Melissa; Campo Catalan, Leslie; Ailawadi, Sarina; Sicinski, Emily M.; Schoonen, Martien; Ingram, Brian; Montrose, David C. (Nutrition & Cancer, 2023)
Dietary protein has been shown to impact physiology and pathophysiology, including inflammation and cancer, effects believed to occur through host and microbe-mediated mechanisms. However, the majority of studies investigating this concept have been conducted in animal models, with less information on the optimal approach, tolerability and biologic effects of modifying protein intake in humans. The current study presents a longitudinal controlled feeding trial carried out in healthy humans to acutely modulate protein intake using individualized diets. Adherence to study diets was monitored through subject-reported electronic picture-based assessments and global metabolomic analysis was performed on serum and stool, following each diet stage. Subjects exhibited strong adherence to study diets, with macronutrient intake meeting study goals during each stage. Metabolomic analysis revealed shifts in both serum and feces in association with modifying protein intake, including reciprocal changes in the abundance of amino acids and amino-acid related compounds, when comparing high to reduced protein stages. Additional fecal metabolite changes consisted of reduced microbial fermentation products following the reduced protein diet stage. Collectively, this study provides a robust method to precisely modify and monitor protein intake in humans, as well as assess corresponding metabolomic alterations.